2010
DOI: 10.1172/jci41490
|View full text |Cite
|
Sign up to set email alerts
|

Rb deletion in mouse mammary progenitors induces luminal-B or basal-like/EMT tumor subtypes depending on p53 status

Abstract: Breast cancer is a highly heterogeneous disease, with several different subtypes being characterized by distinct histology, gene expression patterns, and genetic alterations. The tumor suppressor gene retinoblastoma 1 (RB1) is frequently lost in both luminal-B and triple-negative tumor (TNT; i.e., estrogen receptor-, progesterone receptor-, and human epidermal growth factor receptor 2-negative) breast cancer subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 78 publications
(77 reference statements)
11
126
0
Order By: Relevance
“…Although it has been previously reported that persons with heritable RB were at increased risk of breast cancer, 34 only recently was this finding supported by animal models. 35 As shown here, the RB pathway is compromised in DCIS lesions as detected by elevated p16ink4a expression. Although this finding has been previously described, 6,24 here, we demonstrate that the p16ink4a-positive lesions that exhibit elevated Ki-67 are indeed deficient for RB protein, and such DCIS cases exhibit gene expression profiles indicative of RB loss.…”
Section: Discussionsupporting
confidence: 56%
“…Although it has been previously reported that persons with heritable RB were at increased risk of breast cancer, 34 only recently was this finding supported by animal models. 35 As shown here, the RB pathway is compromised in DCIS lesions as detected by elevated p16ink4a expression. Although this finding has been previously described, 6,24 here, we demonstrate that the p16ink4a-positive lesions that exhibit elevated Ki-67 are indeed deficient for RB protein, and such DCIS cases exhibit gene expression profiles indicative of RB loss.…”
Section: Discussionsupporting
confidence: 56%
“…This model highlighting a role for RB and p53 in stem/progenitor cell populations is compatible with other mouse models of human cancers associated with loss of RB and p53 function, including in the blood compartment, in bones, in the retina and in the mammary epithelium. [35][36][37][38][39] However, the identity of potential neuroendocrine cell progenitors in adult lung tissue has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Rb via two different MMTV-Cre lines induced focal acinar hyperplasia with squamous metaplasia. 70 These lesions progressed into histologically diverse mammary tumors. RNA microarray analysis revealed that the Rb doublemutant mice.…”
Section: Consequences Of Rb Deletion In the Mammary Glandmentioning
confidence: 99%